(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
This research discusses the impact of Uang Panai’ among the community in Lalebata Village, Panca Rijang District, Sidrap Regency. Uang Panai’ is money that must be handed over from the parties of the prospective groom’s family to the prospective bride of the family to finance the wedding ceremony. While dowry is a gift in the form of money or money from men to women as a condition for the validity of marriage according to Islamic teachings. Data is taken from the research process by going directly to the field with qualitative research methods. Data obtained directly from community leaders, religious and community leaders who are considered competent in Lalebata Village, Panca Rijang District, Sidrap Regency.